Cover Feature: 4‐Aminophthalimide Amino Acids as Small and Environment‐Sensitive Fluorescent Probes for Transmembrane Peptides (ChemBioChem 5/2020). (2nd March 2020) - Wörner, Samantha; Rönicke, Franziska; Ulrich, Anne S.; Wagenknecht, Hans‐Achim
Abstract : The cover feature picture shows 4‐aminophthalimide as a fluorescent amino acid side chain in transmembrane EGFR‐like peptides. With its powerful and polarity‐sensitive fluorescence, the chromophore can report its location in the hydrophobic middle or at the surface of membranes by the blue shift in its emission color. More information can be found in the communication by H.‐A. Wagenknecht et al. on page 618 in Issue 5, 2020 (DOI: 10.1002/cbic.201900520 ).